Бюджетний процес Європейського Союзу - Конончук, І.; Kononchuk, I. (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті проаналізовано акти первинного й вторинного права, які регулюють бюджетний процес Європейського Союзу (далі – ЄС). Охарактеризовано принципи формування бюджету ЄС. Визначено систему власних ресурсів ЄС як основного елементу дохідної частини бюджету ЄС. Зазначено, що бюджетний процес ЄС включає такі етапи: розробка проекту бюджету ЄС; розгляд проекту бюджету в Раді та Європейському парламенті; схвалення бюджету; виконання бюджету, контролю за дотриманням бюджетного законодавства. Визначено місце й роль інституцій у бюджетному процесі ЄС.The article analyzes the Acts of the primary and secondary law, governing the budget process of the European Union (hereinafter - the EU). The author reveals the principles of forming the EU budget, laying emphasis on the system of the EU own resources as the main element of the revenue part of the EU budget. EU budgetary process includes the following steps: drafting the EU budget; consideration of the draft budget by the Council and the European Parliament; budget approval; budget execution, monitoring compliance with budget legislation. The place and role of certain institutions in the EU budget process have been defined. The legal regulation of the EU budget process is carried out in accordance with the EU Treaty on the Functioning of the EU and acts of secondary legislation. The EU budget is realized at the expense of the Union’s own resources. Budget revenues and expenditures are to be balanced. The annual EU budget should meet the long-term financial framework plan. The financial framework should ensure the orderly development of EU spending within its own resources. The EU has a three-tier system for monitoring the implementation of the budget, which includes internal control of EU institutions and external control by the Accounting Chamber, as well as political control exercised by the European Parliament and the Council.
Budget Process of the European Union
Keywords: бюджет; бюджетний процес; принципи бюджетного процесу; бюджетна процедура; фінансовий регламент; budget; budget process; principles of budget process; budget procedure; financial regulation